Manganism – Unusual Presentation at Memory Assessment Service - Thilini Ranasinghe (BJPsych Open, 2025)
Aims: More than 200,000 clients are referred to memory assessment annually in the United Kingdom. Alzheimer’s disease and vascular brain injury are found to be the main causes for the memory impairment among these clients. However, a minority of clients present with memory impairment due to metabolic causes.